The Legal Profession in the Age of Digitalization:An outline of Three Potential Transformations in Legal Education - Asmussen, Ida Helene (Utrecht law review, 2019)
There is consensus within the legal profession that it needs to adapt to the on-going digitalisation of the legal market and the changing means of production of the legal commodity. This adaptation will also necessitate a transformation of legal education to assimilate the changes that the legal profession will undergo. The question is, however, how might the legal profession adapt to its digitalisation? In this article, we will describe three possible pathways that the legal profession might follow. These are based on synchronous sociological models of the dynamics of the legal profession and the legal market as well as diachronous sociological descriptions of the history of the legal profession over the past century. In order to concretise these hypotheses, we will focus on the legal profession in three similar countries between which there is some level of comparability: Denmark, Germany and the Netherlands. The three hypothetical pathways are understood to be non-mutually exclusive. We will then answer our core question: how must legal education be transformed to take into consideration the digitalisation of the legal profession? To answer this question, we will describe three possible transformations in legal education that would consider the pathways that the legal profession might pursue to adapt to the digitalisation of its market and the production of its commodity